Pengaruh Promosi, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Susu Sapi Murni Didesa Tlekung Junrejo Batu - Haq, M Ahsanul; Wahono, Budi; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research was conducted to analyze and determine whether or not there is an influence of promotion, price and quality of a product on purchasing decisions. The population and sample in this study were 8 respondents who were consumers of pure cow's milk in Tlekung Junrejo Batu village. Questionnaire collection is the method used to obtain data in this research. The data analysis methods used in this research are Instrument Test, Normality Test, Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis Test, and Coefficient of Determination Test. SPPS was used to analyze this research process. Promotion, price and product quality have a positive and significant influence on the decision to purchase Pure Cow's Milk in Tlekung Junrejo Batu Village. Keywords: Promotion, Price, Product Quality, Purchasing Decision